A novel type I interferon, interferon alphaomega, shows antiviral activity against foot-and-mouth disease virus in vitro. (February 2019) - Li, Shi-fang; Gong, Mei-jiao; Xie, Yin-li; Shao, Jun–jun; Zhao, Fu-rong; Zhang, Yong-guang; Chang, Hui-yun
Abstract: Recently, a novel type I interferon alphaomega (IFN-αω), also known as IFN-μ, was identified. However, the biological activity of IFN-αω remain poorly understood. In this study, the porcine IFN-αω (PoIFN-αω) was expressed, purified, and its antiviral activities assessed by its ability to inhibit the cytopathic effect caused by FMDV on IBRS-2 cells. In addition, q-PCR was used to evaluate the expression of IFN-stimulated genes induced by PoIFN-αω. It was found that PoIFN-αω exerted effective antiviral activity against FMDV pre- and post-infection. Additionally, PoIFN-αω induced the transcription of IFN-stimulated genes, including Mx1, ISG15, OAS1, and PKR genes. Our study reported a new indication of PoIFN-αω as an effective anti-FMDV agent for the first time. Highlights: Porcine IFN-αω was expressed in Escherichia coli and purified with Ni-affinity chromatography successfully. FMDV infection significantly up-regulated IFN-αω expression in vitro. PoIFN-αω exerted effective antiviral activity against FMDV pre- and post-infection. PoIFN-αω induced the transcription of IFN-stimulated genes, including Mx1, ISG15, OAS1, and PKR genes.